2022
DOI: 10.1007/s00423-022-02576-8
|View full text |Cite
|
Sign up to set email alerts
|

Right colectomy from open to robotic — a single-center experience with functional outcomes in a learning-curve setting

Abstract: Purpose Right colectomy (RC) is a frequently performed procedure. Beneath standard conventional open surgery (COS), various minimally invasive techniques had been introduced. Several advantages had recently been described for robotic approaches over COS or conventional laparoscopy. Nevertheless, novel minimally invasive techniques require continuous benchmarking against standard COS to gain maximum patient safety. Bowel dysfunction is a frequent problem after RC. Together with general complicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 60 publications
0
2
1
Order By: Relevance
“…Although the results of this study may cause surgeons to approach with caution, centers around the world have shown lower levels of morbidity in their studies than initially reported (13,14). In their study comparing robotic and convention- (16). In our series, no conversions were reported, and although the operation time was longer in the robot group, it did not affect the postoperative period.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Although the results of this study may cause surgeons to approach with caution, centers around the world have shown lower levels of morbidity in their studies than initially reported (13,14). In their study comparing robotic and convention- (16). In our series, no conversions were reported, and although the operation time was longer in the robot group, it did not affect the postoperative period.…”
Section: Discussioncontrasting
confidence: 49%
“…The technique should also allow for adequate lymph node uptake for staging and therapeutic purposes, with more than 12 lymph nodes for every anatomical segment (17,18). The current literature suggests that there is a higher lymph node harvesting efficiency in minimally invasive robotic surgery for CME performed in RRC cases, but there is insufficient evidence on this topic (16,19). There are also studies reporting a lower number of lymph nodes in robotic surgery despite having an adequate number (15).…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the transient physiological gastrointestinal paralysis that occurs shortly after major abdominal surgery, the development of prolonged postoperative gastrointestinal dysmotility is influenced by multiple factors 3 5 . Perioperative neurogenic dysregulation and inflammatory processes play pivotal roles in the pathogenesis of POI 2 , 6 .…”
Section: Introductionmentioning
confidence: 99%